Paradoxical Reduction in HDL-C With Fenofibrate and Thiazolidinedione Therapy in Type 2 Diabetes: The ACCORD Lipid Trial - Linz, Peter E. (American Diabetes Association, 2014)
OBJECTIVE: To determine the occurrence of extremely low HDL cholesterol (HDL-C) among participants in the Action to Control Cardiovascular Risk in Diabetes (ACCORD) Lipid Trial and to examine the relationship of this finding with treatment with fenofibrate and thiazolidinedione (TZD). RESEARCH DESIGN AND METHODS: The ACCORD Lipid Trial was a randomized, double-blind, placebo-controlled study conducted in patients with type 2 diabetes at 77 clinical centers across the U.S. and Canada in a 5,518-patient subset of the larger 10,251 ACCORD Glycemia Trial. Patients were enrolled from 11 January 2001 to 29 October 2005 and followed until the end of study visits between 1 March and 30 June 2009. Follow-up in the ACCORD Lipid Trial was 4–8 years (mean 4.7 years). Patients were treated with blinded fenofibrate or placebo on a background of simvastatin therapy. The main outcome measures for these descriptive, post hoc analyses was the occurrence of extremely low HDL-C (defined as <25 mg/dL [0.647 mmol/L]) during the trial. RESULTS: Among ACCORD Lipid Trial participants, the occurrence of extremely low HDL-C ever during study follow-up was 106% higher among those randomized to fenofibrate (10.1% fenofibrate vs. 4.9% placebo, P < 0.001). The occurrence of low HDL-C was associated with concurrent treatment with fenofibrate and TZD (7.0% for both vs. 2.2% for neither at 48 months postrandomization). CONCLUSIONS: Idiosyncratic and marked reduction in HDL-C can occur in some patients treated with both fenofibrate and TZD. Practitioners should recognize this important potential idiosyncratic reaction and take appropriate corrective action.